Self-care practices among type II diabetics attending primary health centre, Thiruvallur district, Tamil Nadu - R., Uma Maheshwari; K. R., Sowmiya; S., Kavin (International Journal Of Community Medicine And Public Health, 2017)
Background: Increasing prevalence of diabetes in India is resulting in an epidemiological transition. The care of the people with diabetes is traditionally seen as doctor centered, but the concept of self-care of people with diabetes is a new domain and is proven beneficial in averting long term complications. A diabetes self-care activities measure, together with glycaemic control, can provide essential data for clinicians, diabetes educators, and patients to evaluate and modify treatment. The objective of the study was to determine the practice of self-care activities among people with diabetes attending primary health centre. Methods: A facility-based cross-sectional study was conducted in primary health centre, Tiruvallur health unit division during July–September 2016. A total of 308 patients with >1 year duration of diabetes mellitus (DM) were asked to respond to summary diabetes self-care activities questionnaire after obtaining the consent from them and analysed by proportions. Results: A healthy eating plan on a daily basis was followed by 76.9% (237/308) of the participants, daily exercises for 30 min were followed by 57.1% (176/308), and regular blood sugar monitoring was done by 84.1% (259/308). Regarding the adherence to oral hypoglycemic agents and insulin, daily adherence to medication was seen among 89.7% (226/252) and 75% (42/56) were found to be adherent to insulin injections on a daily basis. Conclusions: Self-care practices were found to be unsatisfactory in fruit and vegetables intake and foot care especially drying in between toes and inspecting inner surface of shoes. Realizing the multi-faceted nature of the problem, a systematic, multipronged and an integrated approach is required for promoting self-care practices among diabetic patients to avert any long-term complications.